Combining the GOR V algorithm with evolutionary information for protein secondary structure prediction from amino acid sequence - Kloczkowski, A.; Ting, K.-L.; Jernigan, R.L.; Garnier, J. (Proteins, structure, function, and bioinformatics, 2002)
We have modified and improved the GOR algorithm for the protein secondary structure prediction by using the evolutionary information provided by multiple sequence alignments, adding triplet statistics, and optimizing various parameters. We have expanded the database used to include the 513 non‐redundant domains collected recently by Cuff and Barton (Proteins 1999;34:508–519; Proteins 2000;40:502–511). We have introduced a variable size window that allowed us to include sequences as short as 20–30 residues. A significant improvement over the previous versions of GOR algorithm was obtained by combining the PSI‐BLAST multiple sequence alignments with the GOR method. The new algorithm will form the basis for the future GOR V release on an online prediction server. The average accuracy of the prediction of secondary structure with multiple sequence alignment and full jack‐knife procedure was 73.5%. The accuracy of the prediction increases to 74.2% by limiting the prediction to 375 (of 513) sequences having at least 50 PSI‐BLAST alignments. The average accuracy of the prediction of the new improved program without using multiple sequence alignments was 67.5%. This is approximately a 3% improvement over the preceding GOR IV algorithm (Garnier J, Gibrat JF, Robson B. Methods Enzymol 1996;266:540–553; Kloczkowski A, Ting K‐L, Jernigan RL, Garnier J. Polymer 2002;43:441–449). We have discussed alternatives to the segment overlap (Sov) coefficient proposed by Zemla et al. (Proteins 1999;34:220–223). Proteins 2002;49:154–166. © 2002 Wiley‐Liss, Inc.